Experiential Avoidance Among Employees in Thi Qar University - Atta Kareem, Prof Dr. Abdul Karim; Jabr, Sajja Khalid (Thi Qar Arts Journal, 2024)
The current research aimed to explore experiential avoidance among employees of Thi Qar University, based on the gender variable (males, females). To achieve the research objectives, the researchers utilized the Jawad (2021) scale, which is grounded in the theory by Hayes et al. (1996). The scale consists of 26 items. The study sample comprised 400 male and female employees, with 157 males and 243 females. The researchers employed SPSS statistical package. The results indicated that the research sample exhibited experiential avoidance, and there were no significant differences between males and females in experiential avoidance. Based on the findings, the researchers arrived at a set of conclusions, recommendations, and proposals.